BADOCAP (Database on goats): advantages and limits - Morand-Fehr P.; Giger-Reverdin S. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
BADOCAP is a reference database of AgroParisTech enclosing 21,500 references (in December 2014) from 174 countries and dealing with all the subjects concerning the goat sector: husbandry, production, products (dairy, meat or hair) and commercial channels. Conditions to include a paper in BADOCAP are its goat specificity (more than 50% of its content must concern a goat subject) and the rigor and originality of its scientific, technical and socio-economical information. BADOCAP covers a broad diversity of subjects, allows searching references by four different methods (one is specific to BADOCAP and gives results more accurate by avoiding interferences with references out of the subject), the easiness of search and the presence of abstracts, which allows answers to a specific question to be obtained more rapidly. 73% of papers are written in English, but the rest has frequently an English abstract. Initially, a high proportion of papers (40-50%) came from “grey documentation” (papers unpublished in acknowledged international reviews) and provided original and interesting information. This proportion has declined steadily for 50 years. The quality, the rigor and the originality of the available information in BADOCAP make an essential tool for goat specialists, decision makers for agricultural policy and goat lovers.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)